LA REPERCUSIÓN DEL CARÁCTER DE FEDERICO GARCÍA LORCA EN LOS PERSONAJES DE YERMA - Al-Afif, Ahmad Husein Issa (European Scientific Journal, ESJ, 2015)
This article is regarded as a new and personal analysis for the famous play of Federico Garcia Lorca Yerma. Most of the literary studies focused on the superficial connotations that Lorca wanted to transfer to the reader about the Spanish society during the first decades of the twentieth century. In this article we focus on the hidden tendency of the author of Yerma and the way he used these characters to reveal his own ideas, specially his homosexuality that could be understood from the attitude of Juan and Yerma at the same time: Juan because he didn’t want to have any children and never think about them, and Yerma because she is regarded as a "dry woman" that will never be a mother forever.